2016
DOI: 10.1097/pts.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Attitudes and Knowledge Toward Incident Reporting in Junior Physicians and Nurses in a District General Hospital

Abstract: This study suggests that junior physicians are lacking in confidence and disengaged with incident reporting. Nurses generally have a more positive and confident view toward patient safety issues and thus are more involved in reporting practices. Health care institutions should focus on promoting a safety culture in the organization through blame-free incident reporting systems. This should include ensuring that junior physicians obtain a comprehensive education in incident reporting and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…In both groups, nurses had submitted the majority of reports, which is consistent with previous studies . However, the portion of reports submitted by doctors was three times higher in serious incidents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In both groups, nurses had submitted the majority of reports, which is consistent with previous studies . However, the portion of reports submitted by doctors was three times higher in serious incidents.…”
Section: Discussionsupporting
confidence: 90%
“…It seems that the employees’ willingness to report incidents increases with severity of incidents, but to our knowledge there are no studies that try to resolve the differences regarding doctors’ willingness to report serious versus nonserious incidents. According to other studies, doctors’ willingness to report safety incidents in general is reduced, for example, by insufficient training on patient safety, fear of blame, embarrassment, fear of consequences for their future career, or the belief that it is not their responsibility to report others’ mistakes . On the contrary, willingness to report increases if the reporting provides a possibility to learn from mistakes, feedback is given, and reports are kept confidential .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea with reporting errors and incidents is to promote solution finding rather than a blame culture . It takes an active role to develop and maintain a patient safety culture characterized by openness and nonblaming, and the department managers should have to shoulder such a role …”
Section: Discussionmentioning
confidence: 99%
“…6 Another study reported that approximately half of physician trainees had ever reported an incident. 7 Commonly cited barriers to reporting include fear of retribution, lack of time, and unclear outcomes or feedback. 810 …”
Section: Introductionmentioning
confidence: 99%